Latinx immigrants raising children in the land of the free: Parenting in the context of persecution and fear. (May 2022) - Cross, Fernanda Lima; Rivas-Drake, Deborah; Aramburu, Jasmin
Anti-immigrant rhetoric generated by the sociopolitical climate under the current U.S. presidential administration has exacerbated the fear of deportation and family separation within the unauthorized Latinx community. Consequently, millions of families, including U.S. citizen children living in mixed-status households, are experiencing stressful environments as they adapt and respond to their social context. This study explored how harsh immigration discourse impacts mixed-status families living in a new-immigrant destination. Twenty-two unauthorized mothers participated in semi-structured interviews regarding their experiences as immigrants raising children in the U.S. Two main themes arose from this analysis: (1) ever-present fear and stress and (2) obeying the law and avoiding others. Parents explained how they had been living in fear since the elections took place, and the different scenarios they had to prepare for in case of deportation. Moreover, some parents choose to minimize conversations around incidents happening in their community to avoid additional stress for children, whereas others addressed children's concerns to reassure them and placate their apprehension. Participants also reported avoiding unnecessary trips outside of the home to prevent interactions with others, especially law enforcement. These results provide important insights regarding the experiences of unauthorized Latinx immigrant parents in the context of sociopolitical adversity. Due to the limited resources often available in new immigrant destinations, social workers must leverage their networks to support families undergoing difficult transitions with special attention to altered family structures and parenting practices. As unauthorized parents attempt to withstand the double burden of basic survival and effective parenting, it is imperative that practitioners provide tools for parents to effectively engage with their children to sustain healthy environments.